Valoración de contratos de proveedores de asistencia médica para la prevención de riesgos financieros de los brokers de seguros - Saltos Saltos, Doris Alexandra (2022)
In this research paper, called "VALUATION OF CONTRACTS OF MEDICAL ASSISTANCE PROVIDERS FOR THE PREVENTION OF FINANCIAL RISKS OF INSURANCE BROKERS" it is about considering if a provider, in which I have a representative part of my clients, decides to close its operations, this would affect me in many ways and could even generate a financial risk to my operation. Talking about risks in life is very complex since there is greater risk greater profitability or utility........